Defining the role of a FYVE domain in the localization and activity of a cAMP phosphodiesterase implicated in osmoregulation in Trypanosoma cruzi - Schoijet, A.C. (2011)
Intracellular levels of cyclic nucleotide second messengers are regulated predominantly by a large superfamily of phosphodiesterases (PDEs). Trypanosoma cruzi, the causative agent of Chagas disease, encodes four different PDE families. One of these PDEs, T. cruzi PDE C2 (TcrPDEC2) has been characterized as a FYVE domain containing protein. Here, we report a novel role for TcrPDEC2 in osmoregulation in T. cruzi and reveal the relevance of its FYVE domain. Our data show that treatment of epimastigotes with TcrPDEC2 inhibitors improves their regulatory volume decrease, whereas cells overexpressing this enzyme are unaffected by the same inhibitors. Consistent with these results, TcrPDEC2 localizes to the contractile vacuole complex, showing strong labelling in the region corresponding to the spongiome. Furthermore, transgenic parasites overexpressing a truncated version of TcrPDEC2 without the FYVE domain show a failure in its targeting to the contractile vacuole complex and a marked decrease in PDE activity, supporting the importance of this domain to the localization and activity of TcrPDEC2. Taking together, the results here presented are consistent with the importance of the cyclic AMP signalling pathway in regulatory volume decrease and implicate TcrPDEC2 as a specifically localized PDE involved in osmoregulation in T. cruzi. © 2010 Blackwell Publishing Ltd.